Long-term stability of limiting nasal alar base width changes with a cinch suture following Le Fort I osteotomy with submental intubation. Issue 11 (November 2017) - Raithatha, R.; Naini, F.B.; Patel, S.; Sherriff, M.; Witherow, H.
Abstract: The aim of this study was to assess the effectiveness of the nasal alar base cinch suture following Le Fort I osteotomy at long-term follow-up. One hundred and forty participants (89 female, 51 male) aged between 16 and 51 years underwent Le Fort I osteotomy with submental intubation. Anthropometric measurements of the nose were taken intraoperatively, immediately postoperative, and for up to 3 years postoperative: the maximum lateral convexity of the alae (Al–Al) and the lateral extremity of the alar base curvature at the alar groove (Ac–Ac). The use of a cinch suture was recorded. The results were analysed using a linear mixed-effects model analysis. One hundred and six participants had cinch sutures and 34 had no cinch sutures. Following Le Fort I osteotomy, there were significant increases in Ac–Ac (by 4.29 mm) and Al–Al (by 3.70 mm) (both P  < 0.0001). Cinch sutures significantly reduced the widths back to preoperative values ( P  < 0.0001). Alar width remained stable over 3 years, with an increase of 0.36 mm for Al–Al ( P  > 0.05) and 1.03 mm for Ac–Ac ( P <  0.05) compared to the postoperative measurement. In conclusion, a cinch suture was helpful in reducing the unwanted alar base width changes, which were found to be relatively stable at 3 years.